Detection of misdiagnosed thyroid dysfunction in early pregnancy: using nonpregnant and pregnancy specific reference intervals - Bandaru Aruna Kumari; Vanumu Chandra Sekhar; Vanumu Vanumu (International Journal of Medical Research and Review, 2016)
Objective: The objective was to assess the prevalence of misdiagnosed thyroid dysfunction during the first trimester of pregnancy when nonpregnant reference intervals used.Materials and Methods: This study, conducted on 233 pregnant women of age between 18 and 35 years during first trimester. Serum thyroid stimulating hormone (TSH), free thyroxine (FT4), thyroperoxidase antibodies (TPO Ab) analyzed and thyroid disorders were grouped, based on the first trimester-specific reference intervals and correlated with nonpregnant reference intervals.Results: The overall prevalence of autoimmunity was 12.4%. The prevalence of subclinical hypothyroid (SCH) was significantly higher than euthyroid when first trimester-specific reference intervals used rather than nonpregnant reference intervals. If the nonpregnant reference intervals were applied to our study group, 27.9% pregnant women with TSH above the first trimester-specific reference intervals would not have been identified and misclassified as euthyroid. 22.7% would have missed the diagnosis as SCH. 5.2% with low FT4 levels, among this 3% and 2.1% would not have been identified as overt hypothyroid and isolated hypothyroxinemia. The relative risk of autoimmunity was significantly 3.66 times more in SCH than euthyroid, when first trimester-specific reference intervals used.Conclusion: Misdiagnosis of SCH, overt hypothyroid and autoimmune thyroid disorders occurred during the first trimester of pregnancy if nonpregnant reference intervals used. Undiagnosed hypothyroidism in pregnant women may adversely affect their fetuses; therefore the early and appropriate detection of thyroid dysfunction require reliable pregnancy-specific reference intervals of the thyroid hormones.